Mass of Spiral Galaxies by Means of a Maximum Disc Model - Framsol López-Suspes; Guillermo A González (Universitas Scientiarum)
Maximum disc mass models for a set of spiral galaxies from the Ursa Major Cluster are presented. We construct the models using the Hunther method and the particular solutions are chosen in such away that the circular velocities are adjusted very accurately to the observed rotation curves of some specific spiral galaxies. Under the maximum disc hypothesis, we consider that the rotation curves of the analyzed galaxies can be modeled with only the contribution of the disc. This implies that it is not necessary to consider the contribution of the dark matter halo in the inner part of the spiral. In this way, the models reproduce the global behavior of the rotation curves in the great majority of galaxies. Producing good adjustments to calculate the total mass of these galaxies, and yielding values of the order of 1010M0. Based on the verticalstability criterion presented by Viera & Ramos-Caro(2016), we find that all the galaxies analyzed present a vertically stable behavior.On the other hand, from the analysis of the epicyclic frequency we find that al lthe models exhibit mainly a radial stable behaviour except at the edge of the disc.